1979
DOI: 10.1177/1077727x7900700404
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Clothing and Self‐Concept of Physically Handicapped and Able‐Bodied University Men and Women

Abstract: The purposes of this study were to ascertain the extent to which students with physical handicaps have clothing attitudes that differ from able‐bodied students, and to investigate the relationship between self‐concept and clothing attitudes. Data were collected from 35 handicapped and 76 able‐ bodied university students. Handicapped students were defined as those who had orthopedic dis abilities and were confined to wheelchairs. The clothing attitude variables were appearance, fash ion, management, comfort, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Researchers in the 1970s (e.g., Ahrbeck & Friend, 1976;Newton, 1976;Kernaleguen, 1978;Feather, Martin, & Miller, 1979;Hoffman, 1979;Shannon & Reich, 1979) discussed issues of comfort, ease in dressing, and fabric and garment durability, as well as the use of clothing to conceal disabilities. Most of them argued that while clothing care and adaptations are often necessary for ease in dressing, these same adaptations make the clothes look different from garments worn by everyone else.…”
mentioning
confidence: 99%
“…Researchers in the 1970s (e.g., Ahrbeck & Friend, 1976;Newton, 1976;Kernaleguen, 1978;Feather, Martin, & Miller, 1979;Hoffman, 1979;Shannon & Reich, 1979) discussed issues of comfort, ease in dressing, and fabric and garment durability, as well as the use of clothing to conceal disabilities. Most of them argued that while clothing care and adaptations are often necessary for ease in dressing, these same adaptations make the clothes look different from garments worn by everyone else.…”
mentioning
confidence: 99%
“…Clothing is a form of nonverbal communication and helps individuals in boosting their self-esteem (Aldredge, 1973;Bader, 1983;Calhoun & Morse, 1977;Feather, Martin, & Miller, 1979;Schneider, 1974). However, conflicting viewpoints exist as to whether fashionable or classic styles of clothing would enhance individuals' cognitive and physical selves.…”
mentioning
confidence: 99%
“…Feather et al (1979) found expectations were lower for disabled students who expressed less dissatisfaction with clothing available in the market than did able-bodied students. The low ranking of importance given both of these suggests an acceptance of an existing situation even though disabled consumers have expressed need for specialized clothing.…”
Section: Discussionmentioning
confidence: 84%
“…Reich (1975) explained that clothing can enhance a person's body and reduce the threat of psychological insecurity. Feather, Martin, and Miller (1979) reported clothing appearance was as important to disabled students as to able-bodied students. Feather, Martin, and Miller (1979) reported clothing appearance was as important to disabled students as to able-bodied students.…”
Section: Review Of Current Literaturementioning
confidence: 94%